2020
DOI: 10.1017/s0033291719004094
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between antihypertensive medications and mood disorders: analysis of linked healthcare data for 1.8 million patients

Abstract: Background Recent work suggests that antihypertensive medications may be useful as repurposed treatments for mood disorders. Using large-scale linked healthcare data we investigated whether certain classes of antihypertensive, such as angiotensin antagonists (AAs) and calcium channel blockers, were associated with reduced risk of new-onset major depressive disorder (MDD) or bipolar disorder (BD). Method Two cohorts of patients treated with antihypertensives were identified from Scottish … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 31 publications
5
26
0
Order By: Relevance
“…However, experimental data suggest that RAS inhibitors may have mood-elevating effects (111). Also, some (112)(113)(114), but not all (115,116), explorative observational studies have suggested that RAS inhibitors may protect against depression.…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…However, experimental data suggest that RAS inhibitors may have mood-elevating effects (111). Also, some (112)(113)(114), but not all (115,116), explorative observational studies have suggested that RAS inhibitors may protect against depression.…”
Section: Pharmacological Interventionsmentioning
confidence: 99%
“…In a Scottish hospital database, the lowest risks of admission for depressive illness over a 5-year period occurred in patients treated with ARBs or ACEIs compared to other AHTs 1 . In a subsequent much larger study, Shaw and colleagues 2 showed that monotherapy with ARBs or ACEIs was associated with lower rates of a first diagnosis of depression compared to other AHTs, with β-blockers being associated with the highest risk. These authors also found that a diagnosis of bipolar disorder was less common with ARBs and ACEIs.…”
Section: Introductionmentioning
confidence: 99%
“…However, an enriched Flavonifractor in major depressive disorder [45] and bipolar disorder [46] could also link the relationship between β-blockers and major depressive disorder or bipolar disorder. [49] We also identi ed a potential link between β-blocker use and the genus Tyzzerella in the PS-matched cohort. Importantly, Tyzzerella was enriched in those with a high cardiovascular risk pro le.…”
Section: Discussionmentioning
confidence: 99%